The impact of high world oil prices to small and medium enterprise exporters / Fairus Mohamad Yazid - Mohamad Yazid, Fairus (Faculty of Business and Management, 2006)
Nowadays the increasing price of oil is very high compared to the previous price. This issue will have a significant impact to our daily life such as increasing cost of petrol and the increasing of world oil price also give an impact to the business in all over the world.